The One Piece Flag as a Silent Protest: A Semiotic Study of Popular Culture Symbolism in Contemporary Indonesia - Yuda Syah Putra; Irpan Riana (Jomantara Indonesian Journal of Art and Culture, 2026)
The phenomenon of raising the One Piece flag, particularly the Straw Hat Pirates' Jolly Roger, in Indonesian public spaces has become a focal point in socio-cultural discussions. Originally a symbol from a Japanese anime, it has transcended its role as mere fandom expression to become a medium for conveying societal aspirations and frustrations, particularly among the younger generation, regarding Indonesia's socio-political realities. This study employs Roland Barthes' semiotic approach to analyze the denotative, connotative, and modern mythic meanings embedded in the symbol. Findings reveal that the One Piece flag not only represents freedom and adventure as in its fictional narrative but also symbolizes resistance against injustice, collective solidarity, and subtle critique of systems perceived as unresponsive to public needs. Social media plays a pivotal role in disseminating and normalizing the flag's new meanings while sparking diverse reactions from the public and authorities. Some view it as a threat to national unity, while others interpret it as a form of free expression and "silent protest." This phenomenon reflects a crisis of trust in national symbols and a shift in collective identity from state-led narratives to pop culture symbols that resonate more with youth aspirations. The study highlights the potential of popular culture as a tool for articulating identity and social change, emphasizing the need for a communicative approach to understand unconventional expressions in the digital era.